Pairwise diversity and tMRCA as potential markers for HIV infection recency. Issue 6 (February 2017) - Moyo, Sikhulile; Wilkinson, Eduan; Vandormael, Alain; Wang, Rui; Weng, Jia; Kotokwe, Kenanao P.; Gaseitsiwe, Simani; Musonda, Rosemary; Makhema, Joseph; Essex, Max; Engelbrecht, Susan; de Oliveira, Tulio; et al.
Abstract : Abstract: Intrahost human immunodeficiency virus (HIV)-1 diversity increases linearly over time. We assessed the extent to which mean pairwise distances and the time to the most recent common ancestor (tMRCA) inferred from intrahost HIV-1C env sequences were associated with the estimated time of HIV infection. Data from a primary HIV-1C infection study in Botswana were used for this analysis (N = 42). A total of 2540 HIV-1C env gp120 variable loop region 1 to conserved region 5 (V1C5) of the HIV-1 envelope gp120 viral sequences were generated by single genome amplification and sequencing, with an average of 61 viral sequences per participant and 11 sequences per time point per participant. Raw pairwise distances were calculated for each time point and participant using the ape package in R software. The tMRCA was estimated using phylogenetic inference implemented in Bayesian Evolutionary Analysis by Sampling Trees v1.8.2. Pairwise distances and tMRCA were significantly associated with the estimated time since HIV infection (both P  < 0.001). Taking into account multiplicity of HIV infection strengthened these associations. HIV-1C env- based pairwise distances and tMRCA can be used as potential markers for HIV recency. However, the tMRCA estimates demonstrated no advantage over the pairwise distances estimates.